Gyrotron development for high-power, long-pulse electron cyclotron heating and current drive at two frequencies in JT-60SA and its extension toward operation at three frequencies. (30th April 2015) - Kobayashi, T.; Yokokura, S. Moriyama K.; Sawahata, M.; Terakado, M.; Hiranai, S.; Wada, K.; Sato, Y.; Hinata, J.; Hoshino, K.; Isamaya, A.; Oda, Y.; Ikeda, R.; et al.
Abstract: A gyrotron enabling high-power, long-pulse oscillations at both 110 and 138 GHz has been developed for electron cyclotron heating (ECH) and current drive (CD) in JT-60SA. Oscillations of 1 MW for 100 s have been demonstrated at both frequencies, for the first time in the world as a gyrotron operating at two frequencies. The optimization of the anode voltage, or the electron pitch factor, using a triode gun was a key to obtain high power and high efficiency at two frequencies. It was also confirmed that the internal losses in the gyrotron were sufficiently low for expected long pulse operation at the higher power level of ∼1.5 MW. Another important result is that an oscillation at 82 GHz, which enables use of fundamental harmonic waves in JT-60SA while the other two frequencies are used as second harmonics waves, was demonstrated up to 0.4 MW for 2 s. These results of the gyrotron development significantly contribute to enhancing the operation regime of the ECH/CD system in JT-60SA.